2021
DOI: 10.1094/pdis-05-20-1076-re
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Identification of Pectobacterium carotovorum subsp. brasiliensis and Dickeya dianthicola Causing Blackleg in Some Potato Fields in Serbia

Abstract: Blackleg outbreaks were noticed on three fields (total c. 100 ha) during two consecutive years (2018, 2019) in one of the main potato growing areas in Serbia (Bačka region, Vojvodina). The percentage of infected plants reached 40-70% with 10.5% to 44.7% yield reductions. From the three fields out of 90 samples Pectobacterium carotovorum subsp. brasiliensis was most frequently identified and diagnosed as causal agent of potato blackleg in Serbia for the first time (29 isolates). Dickeya dianthicola was a less f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Scotch Cara and may indicate the susceptibility of the reported cultivar for soft rot and/ or blackleg infection. Furthermore, the results of this current study highlight a concordance to results were reported by Marković et al (2021) stated that two types of tissue decomposition could be notified for these diseases: the first group of isolates (Like E3, E4 and E7 for Spunta variety, and E4 and E7 for Desiree variety) produced cream-colored rotting tissue with dark brown margins in the zone between the healthy and decomposed tissue, and the second group (Such as isolates E5 for Spunta variety, and E3 and E5 for Desiree variety) devastated the tissue causing cream-colored rotting but with no visible margins.…”
Section: Resultssupporting
confidence: 93%
“…Scotch Cara and may indicate the susceptibility of the reported cultivar for soft rot and/ or blackleg infection. Furthermore, the results of this current study highlight a concordance to results were reported by Marković et al (2021) stated that two types of tissue decomposition could be notified for these diseases: the first group of isolates (Like E3, E4 and E7 for Spunta variety, and E4 and E7 for Desiree variety) produced cream-colored rotting tissue with dark brown margins in the zone between the healthy and decomposed tissue, and the second group (Such as isolates E5 for Spunta variety, and E3 and E5 for Desiree variety) devastated the tissue causing cream-colored rotting but with no visible margins.…”
Section: Resultssupporting
confidence: 93%
“…Using traditional isolation and molecular characterization in the same eld in Northern Serbia during 2018, combined infection of P. carotovorum subsp. brasiliensis and D. dianthicola was determined (Marković et al 2020) while the Dickeya spp. was found at the limit of detection in metabarcoding samples.…”
Section: Discussionmentioning
confidence: 99%
“…According to the whole dataset with singletons excluded, the Dickeya genus was not found, although bacteria belonging to the D. dianthicola were isolated and identi ed from the same eld (Marković et al 2020).…”
Section: Bacterial Community Compositionmentioning
confidence: 99%
“…Multilocus sequence analysis (MLSA) was performed with a total of 36 randomly selected isolates, with three per year of isolation, location, and potato cultivar (Table 1). Total DNA was extracted using the modified CTAB protocol described by Marković et al (2021).…”
Section: Methodsmentioning
confidence: 99%